Semileptonic decays of anti-triplet charmed baryons - Chao-Qiang Geng; Chia-Wei Liu; Tien-Hsueh Tsai; Shu-Wei Yeh (Physics Letters B, 2019)
We study the semileptonic decays Bc→Bnℓ+νℓ where Bc(n) is the anti-triplet-charmed (octet) baryon with the SU(3)f flavor symmetry and helicity formalism. In particular, we present the decay branching ratios of Bc→Bnℓ+νℓ in three scenarios: (a) an exact SU(3)f symmetry with equal masses for the anti-triplet-charmed (octet) baryon states of Bc (Bn), (b) SU(3)f parameters without the baryonic momentum-transfer dependence, and (c) SU(3)f with baryonic transition form factors in the heavy quark limit. We show that our results are all consistent with the existing data. Explicitly, we predict that B(Ξc+→Ξ0e+νe)=(11.9±1.3,9.8±1.1,10.7±0.9)×10−2 and B(Ξc0→Ξ−e+νe)=(3.0±0.3,2.4±0.3,2.7±0.2)×10−2 in the scenarios (a), (b) and (c) agree with the data of (14.0−8.7+8.3)×10−2 and (5.6±2.6)×10−2 from the CLEO Collaboration, respectively. In addition, we obtain that B(Λc+→ne+νe)=(2.8±0.4,4.9±0.4,5.1±0.4)×10−3 in (a), (b) and (c). We also examine the longitudinal asymmetry parameters of α(Bc→Bnℓ+νℓ), which are sensitive to the different scenarios with SU(3)f. Some of the decay branching ratios and asymmetries can be observed by the ongoing experiments at BESIII and LHCb as well as the future searches by BELLEII.